Cardamom Essential Oil Extract Suppress the Progression of Triple-Negative Breast Cancer 4T1 Cell Line - Ahmad Syauqy Tafrihani; Nisa Ul Hasanah; Dhiya Ulhaq Salsabila; Ratih Kurnia Wardani; Ummi Maryam Zulfin; Muthi' Ikawati; Edy Meiyanto; Riris Istighfari Jenie (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Cardamom (Amomum cardamom) essential oil (CEO) contains monoterpenes with antioxidant activity and is reported to exhibit anticancer activity against some cancer cell lines. Triple-negative breast cancer (TNBC) has the lowest prognosis among breast cancer types due to its aggressive characteristics. This study was conducted to explore the potency of CEO in inhibiting 4T1 cell proliferation and migration and compared its activity to sappan (Caesalpinia sappan) wood extract (CSE).METHODS: We used the 4T1 cell line as the TNBC cell model and tested the cytotoxicity of CEO by using a trypan blue exclusion assay. We studied the senescence induction ability of CEO using SA-β-Gal assay, the migratory inhibition activity using scratch wound healing assay, and inhibition of matrix metalloproteinase 9 (MMP-9) expression using gelatin zymography. RESULTS: CEO showed cytotoxicity toward 4T1 cells with the IC50 values of 60 µg/mL. CEO at ½ IC50 and IC50 concentration significantly increased cell senescence, but CSE did not. CEO at IC50 also reduced cell ability to migrate and also considerably reduced MMP-9 activity. Moreover, these activities related to the inhibition of the cell metastasis process were weaker compared than that of CSE.CONCLUSION: CEO showed potency as a chemopreventive agent on the TNBC 4T1 cell line model with moderate cytotoxicity. CEO induced 4T1 cell senescence, inhibited cell migration and suppressed MMP-9 expression.KEYWORDS: Amomum cardamom, Caesalpinia sappan, 4T1, senescence, cell migration, triple-negative breast cancer